Work Discipline of Civil Servants at the Bulukumpa Sub-district Office, Bulukumba Regency - Nasnidar Nasnidar; Risma Niswaty; Isgunandar Isgunandar (Journal of Public Policy and Local Government (JPPLG), 2024)
Discipline is one of the important aspects that supports the quality of performance of a Civil Servant (PNS), this study aims to find out how the work discipline of civil servants in the Bulukumpa Sub-district Office, Bulukumba Regency. The type of research used in this study is a qualitative descriptive research type and for the data collection techniques used, namely observation, interview and documentation techniques with three informants, namely employees of the Bulukumpa Sub-district Office, Bulukumba Regency. The results of this study show that employee discipline at the Bulukumpa Sub-district Office, Bulukumba Regency is still lacking. This can be seen from attendance, responsibility, attitudes, and norms. Where the attendance of employees has not been in accordance with the regulations that have been set and the results of observation as evidenced through the recap of the attendance list, the implementation of employee responsibilities that have been included in the category is very good, but the attitude of employees who are still categorized as poor is evidenced by the use of office uniforms that are not orderly so that they are not in accordance with the established regulations. Then the norms or compliance with the regulations are still not good, as seen from the fact that there are still some employees who do not comply and receive reprimands from the leadership. The results of this study are still not in accordance with what is expected based on discipline indicators